Some Reflections on the Identification of the Concept of Childhood among the Ancient Nahuas based on Colonial Documents - Díaz Barriga Cuevas, Alejandro (2023)
This paper focuses on the main aspects to consider in the historical research on pre-Hispanic Childhood based on colonial documents. I analyze the mentality of the chroniclers, the different ideologies they had, the life cycles, and the models they followed to write their works, in which they described the Indigenous childhood using their own parameters. Also, I include some examples that show how Indigenous people incorporated Western models in the descriptions of their own past. Finally, I analyze the words that the Europeans used to define children, some of which have different meanings nowadays.